Oncological outcomes of compartmental surgery and wide local excision in oral tongue and floor of the mouth cancer. (December 2022) - Missale, Francesco; Marchi, Filippo; Iandelli, Andrea; Subramaniam, Narayana; Dokhe, Yogesh; Sampieri, Claudio; Mattavelli, Davide; Bresciani, Lorenzo; Carobbio, Andrea Luigi Camillo; Grammatica, Alberto; Thankappan, Krishnakumar; Iyer, Subramania; et al.
Highlights: Anatomical complexity of the tongue leads challenges in treating tongue cancer. WLE appears to be the technique that guarantees clear microscopic margins. CTS allows surgeons to perform safe, standardized, and effective resections. Variables reflecting tumor biology play the main role in treatment outcomes. The most adequate approach revolves around 3D circumferential tumor clearance. Abstract: Objectives: Oral tongue carcinomas represent more than half of the tumors arising in the oral cavity, a site with a high cancer specific mortality and impact on quality of life. Current guidelines are lacking for a standardized surgical approach of these tumors. The aim of this study is to compare two currently adopted surgical strategies, compartmental surgery (CTS) and wide local excision (WLE), with loco-regional control as the main oncological endpoint. Materials and methods: An observational retrospective multicentric study was carried out enrolling a cohort of patients affected by oral tongue or floor of the mouth squamous cell carcinoma and surgically treated in 4 international tertiary referral centers. Survival analysis was performed by propensity-score matching approach and multivariable Cox regression analysis. Results: A cohort of 933 patients was enrolled. CTS was applied in 113 patients (12.1%) and WLE in 820 (87.9%). Analyzing a propensity-score matched cohort (98 CTS vs. 172 WLE) and applying a survival multivariable modeling strategy on the whole cohort, both confirmed that CTS and WLE are comparable and oncologically safe. Parameters such as number of positive lymph nodes, depth of invasion, and lymphovascular invasion still represent the key prognosticators. Conclusion: The main goals for surgical resection of oral cancer remain its three-dimensional circumferential clearance with adequate margins and en-bloc removal of the tumor-lymph node tract, independently of the technique adopted (CTS or WLE). Further prospective studies including quality of life evaluation are needed to better understand if one of these approaches can provide superior functional outcomes.